Fenomena Flexing dalam Interaksi Agama dan Publik: Studi Kasus Kehidupan Pendakwah Ustaz Solmed - Laelani, Rizki (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
This study examines the phenomenon of "flexing" within Islamic proselytization (dakwah) by analyzing its application as a communication strategy based on Ustaz Solmed's perspective. The research seeks to address how flexing, commonly associated with showcasing material wealth or achievements, can be utilized in dakwah without contradicting Islamic principles. Employing qualitative methods through literature reviews and case studies, the study identifies the dual nature of flexing in inspiring societal success while cautioning against arrogance and ostentation (riya). The findings reveal that flexing, when used with the right intentions, aligns with Islamic teachings as a form of gratitude and motivation for collective betterment. However, its implementation requires ethical considerations to ensure it does not promote materialism or social inequality. This research highlights the importance of balancing contemporary communication trends with traditional Islamic values, offering insights into adapting dakwah strategies for modern audiences.